Volume and in-hospital mortality after emergency abdominal surgery: a national population-based study. Issue 11 (2nd November 2019) - Nally, Deirdre M; Sørensen, Jan; Valentelyte, Gintare; Hammond, Laura; McNamara, Deborah; Kavanagh, Dara O; Mealy, Ken
Abstract : ​Objectives: Emergency abdominal surgery (EAS) refers to high-risk intra-abdominal surgical procedures undertaken for acute gastrointestinal pathology. The relationship between hospital or surgeon volume and mortality of patients undergoing EAS is poorly understood. This study examined this relationship at the national level. ​Design: This is a national population-based study using a full administrative inpatient dataset (National Quality Assurance Improvement System) from publicly funded hospitals in Ireland. ​Setting: 24 public hospitals providing EAS services. ​Participants and Interventions: Patients undergoing EAS as identified by primary procedure codes during the period 2014–2018. ​Main outcome measures: The main outcome measure was adjusted in-hospital mortality following EAS in publicly funded Irish hospitals. Mortality rates were adjusted for sex, age, admission source, Charlson Comorbidity Index, procedure complexity, organ system and primary diagnosis. Differences in overall, 7-day and 30-day in-hospital mortality for hospitals with low (<250), medium (250–449) and high (450+) volume and surgical teams with low (<30), medium (30–59) and high (60+) volume during the study period were also estimated. ​Results: The study included 10 344 EAS episodes. 798 in-hospital deaths occurred, giving an overall in-hospital mortality rate of 77 per 1000 episodes. There was no statistically significant difference in adjusted mortality rate between low and high volume hospitals. Low volume surgical teams had a higher adjusted mortality rate (85.4 deaths/1000 episodes) compared with high volume teams (54.7 deaths/1000 episodes), a difference that persisted among low volume surgeons practising in high volume hospitals. ​Conclusion: Patients undergoing EAS managed by high volume surgeons have better survival outcomes. These findings contribute to the ongoing discussion regarding configuration of emergency surgery services and emphasise the need for effective clinical governance regarding observed variation in outcomes within and between institutions.